2007
DOI: 10.1016/j.bcmd.2007.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Gadd45 in the response of hematopoietic cells to genotoxic stress

Abstract: Gadd45 genes have been implicated in stress signaling in response to physiological or environmental stressors, which results in either cell cycle arrest, DNA repair, cell survival and senescence, or apoptosis. Evidence accumulated implies that Gadd45 proteins function as stress sensors is mediated by a complex interplay of physical interactions with other cellular proteins that are implicated in cell cycle regulation and the response of cells to stress. These include PCNA, p21, cdc2/cyclinB1, and the p38 and J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 60 publications
3
78
1
Order By: Relevance
“…The DNA damage-induced transcription of this gene is mediated by both p53-dependent and p53-independent mechanisms. 32 On the other hand, our results found a large number of genes differentially expressed between MGUS and MM patients, which is not consistent with a previous report showing that most gene expression changes occur between NPC and MGUS with less than 100 genes differentially expressed between MGUS and MM. 10 Probably, the number of cases analyzed and the new version of Affymetrix array used in our study, which interrogates approximately 28,000 well-annotated genes, could explain these differences.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The DNA damage-induced transcription of this gene is mediated by both p53-dependent and p53-independent mechanisms. 32 On the other hand, our results found a large number of genes differentially expressed between MGUS and MM patients, which is not consistent with a previous report showing that most gene expression changes occur between NPC and MGUS with less than 100 genes differentially expressed between MGUS and MM. 10 Probably, the number of cases analyzed and the new version of Affymetrix array used in our study, which interrogates approximately 28,000 well-annotated genes, could explain these differences.…”
Section: Discussioncontrasting
confidence: 99%
“…31 The upregulation of BAG3 and GADD45B in MM also contribute to the antiapoptotic state of this disease. 32,33 Moreover, APAF1…”
Section: Genes Differentially Expressed Between Mgus and MMmentioning
confidence: 99%
“…Gadd45 binds to proliferating cell nuclear antigen at several residues, thereby causing cell cycle arrest. Although Gadd45a/b induction can induce cell apoptosis under some conditions, the Gadd45g gene acts as a critical and essential promoter of cell apoptosis at all times [16,18,43]. Studies by Pippin et al demonstrated that DNA damage was a novel response to sublytic complement C5b-9-induced injury in podocytes [42].…”
mentioning
confidence: 99%
“…The genes encoding the α, β and γ isoforms of Gadd45 are respectively located at 1p31.2, 19p13.3 and 9q22.1 in the human genome, and they have different promoters and introns (Kastan et al, 1992;Jung et al, 2000;Lefort et al, 2001;Furukawa-Hibi et al, 2002;Thyss et al, 2005). Each gene is induced by a distinct subset of environmental and physiological stresses (Liebermann and Hoffman, 2007). The three Gadd45 proteins are small (18 kDa), highly acidic and evolutionarily conserved.…”
Section: Introductionmentioning
confidence: 99%